BERMAIN SEPEDA UNTUK MELATIH KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN - Mahkamah Brantasari (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
Playing A Bike To Train The Rude Motor Ability Of Children Age 5-6 Years Old. During the Covid-19 pandemic, children with active characteristics will of course feel bored with games in the house that are less free. And children feel limited in exploring physical activities related to gross motor skills. Children at an early age are very important to carry out physical movements with the aim of stimulating the physical growth of children's motor skills, both fine and gross motor skills. To make children excited about doing physical activities, one of them is by inviting them to ride bikes together. In a joint cycling situation, direct observations can be made and also ask what children feel when playing a bicycle, the research conducted by the author uses a case study of a child aged 5-6 years who plays a two-wheeled bicycle with a focus on training the child's gross motor skills. , namely by locomotor, non-locomotor, and manipulative movements. From what has been done during the activity of playing bicycles, all of the movements made by children when playing bicycles have all referred to the gross motor skills of children, especially children aged 5-6 years.